Understanding Anaplasmataceae pathogenesis using “Omics” approaches - Pruneau, Ludovic; Moumène, Amal; Meyer, Damien F.; Marcelino, Isabel; Lefrançois, Thierry; Vachiéry, Nathalie (Frontiers in Cellular and Infection Microbiology, 2014)
This paper examines how “Omics” approaches improve our understanding of Anaplasmataceae pathogenesis, through a global and integrative strategy to identify genes and proteins involved in biochemical pathways key for pathogen-host-vector interactions. The Anaplasmataceae family comprises obligate intracellular bacteria mainly transmitted by arthropods. These bacteria are responsible for major human and animal endemic and emerging infectious diseases with important economic and public health impacts. In order to improve disease control strategies, it is essential to better understand their pathogenesis. Our work focused on four Anaplasmataceae, which cause important animal, human and zoonotic diseases: Anaplasma marginale, A. phagocytophilum, Ehrlichia chaffeensis and E. ruminantium. Wolbachia spp. an endosymbiont of arthropods was also included in this review as a model of a non-pathogenic Anaplasmataceae. A gap analysis on “Omics” approaches on Anaplasmataceae was performed, which highlighted a lack of studies on the genes and proteins involved in the infection of hosts and vectors. Furthermore, most of the studies have been done on the pathogen itself, mainly on infectious free-living forms and rarely on intracellular forms. In order to perform a transcriptomic analysis of the intracellular stage of development, researchers developed methods to enrich bacterial transcripts from infected cells. These methods are described in this paper. Bacterial genes encoding outer membrane proteins, post-translational modifications, eukaryotic repeated motif proteins, proteins involved in osmotic and oxidative stress and hypothetical proteins have been identified to play a key role in Anaplasmataceae pathogenesis. Further investigations on the function of these outer membrane proteins and hypothetical proteins will be essential to confirm their role in the pathogenesis. Our work underlines the need for further studies in this domain and on host and vector responses to infection